2008
DOI: 10.1111/j.1745-6916.2008.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Unconscious Mind

Abstract: The unconscious mind is still viewed by many psychological scientists as the shadow of a "real" conscious mind, though there now exists substantial evidence that the unconscious is not identifiably less flexible, complex, controlling, deliberative, or action-oriented than is its counterpart. This "conscious-centric" bias is due in part to the operational definition within cognitive psychology that equates unconscious with subliminal. We review the evidence challenging this restricted view of the unconscious em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
464
1
14

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(490 citation statements)
references
References 30 publications
11
464
1
14
Order By: Relevance
“…Here, it is the social role of automatic imitation that creates trouble for the inheritance system hypothesis. Research in social psychology has shown the pervasive influence of various broadly imitative effects on action, in a way that is not subject to conscious control (Bargh & Ezequiel 2008). These are effects of a different kind than the goal-directed imitation discussed earlier.…”
Section: Recent Developments In the Evidence (A) High-fidelity Transmmentioning
confidence: 98%
“…Here, it is the social role of automatic imitation that creates trouble for the inheritance system hypothesis. Research in social psychology has shown the pervasive influence of various broadly imitative effects on action, in a way that is not subject to conscious control (Bargh & Ezequiel 2008). These are effects of a different kind than the goal-directed imitation discussed earlier.…”
Section: Recent Developments In the Evidence (A) High-fidelity Transmmentioning
confidence: 98%
“…The attempt to better understand these processes has led to an operational definition of unconsciousness as 'a lack of awareness regarding the influences or effects of a triggering stimulus.' 5,6 The psychologist and Nobel Prize winner in economics, Daniel Kahneman, has shown elegantly how our unconscious minds control our judgement and behaviour -and that we are 'hardwired' to ignore this fact. An evolutionary explanation for our brains working this way is easy to accept if one considers the advantages, for survival in a hostile environment, of quick and intuitive actions.…”
Section: The Conscious Mind's Bias Of Being In Controlmentioning
confidence: 99%
“…5 One channel for behavioural priming is through the olfactory system, as odour has been shown to influence behaviour. Specifically, a fresh lemon fragrance, which invokes mental models of hygiene and cleanliness, has been demonstrated as having a positive effect on hand hygiene behaviour in a simulated environment.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…This is in stark contrast to subliminal priming that typically involves presenting primed material on a computer below the field of focal vision so that an individual does not report any awareness of it. Bargh and Marsella (2008) have criticized the use of subliminal priming because of its lack of ecological validity. They argued that subliminal stimuli do not naturally occur, and further that they are too weak or brief in natural settings to have an enduring effect on behavior.…”
mentioning
confidence: 99%